A Study of Machine Learning and IoT in Manufacturing industries - R.Gore, R; D. Patil, J (International Journal of Computer Sciences and Engineering, 2025)
The last decade has witnessed a shift in manufacturing processes from basic automation and event control to smart systems that create virtual blueprint which is transformed into real-world product. This transformation, dubbed as Industry 4.0 is an optimization of the practices which took place previously in the industries. The driving force behind this revolution has been machine learning and Internet of Things (IoT). Internet of Things is a term for devices that have the capability to connect and collaborate amongst themselves to minimize human intervention. In order to further enhance this connectivity, machine learning techniques are being implemented, that enable decision making through data analysis. This paper aims to demonstrate the use of these techniques in the manufacturing industry in the context of Industry 4.0. It will also shed light upon some of the upcoming applications of the same, including intelligently forecasting the estimated demand, detecting the anomalies within the product, optimizing manufacturing processes and securing the entire framework. The future use cases of this technology will be addressed in this paper.